MARKETING STRATEGY FOR FURNITURE PRODUCED FROM PRISONER WORK TRAINING AT CLASS IIA BINJAI PENITENTIARY - Girsang, Pido Sodipto Astanja; Nugroho, Fathurrahman (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to analyze the marketing strategy of furniture at the Class IIA Correctional Facility in Binjai based on the 4P marketing mix theory (Product, Price, Place, Promotion) and to identify the challenges faced. A qualitative approach was employed, with data collection through observation and interviews. The results show that although the marketing strategy has been implemented, its execution is not yet optimal. The products offered are of high quality and come with a warranty, but limited infrastructure and the lack of skilled labor are major obstacles. Additionally, workspace constraints and shipping processes often disrupt production. Promotion and the placement of outlets in strategic locations need to be improved, while price pressure from buyers and the obligation to meet Non-Tax State Revenue (PNBP) requirements add to the challenges. This study recommends training officers in marketing and increasing budgets and facilities to enhance marketing effectiveness and the success of the products in the market. Keywords: Marketing Strategy; 4P Marketing Mix; Correctional Facility